Development of a syn‐Selective Mannich Reaction of Aldehydes with Propargylic Imines by Dual Catalysis: Asymmetric Synthesis of Functionalized Propargylic Amines. Issue 21 (13th April 2016) - Lapuerta, Irati; Vera, Silvia; Oiarbide, Mikel; Palomo, Claudio
Abstract: Direct coupling of enolizable aldehydes with C ‐alkynyl imines is realized affording the corresponding propargylic Mannich adducts of syn configuration, thus complementing previous methods that gave access to the anti ‐isomers. The combination of proline and a urea Brønsted base cocatalyst is key for the reactions to proceed under very mild conditions (3–10 mol % catalyst loading, dichloromethane as solvent, −20 °C, 1.2 molar equivalents of aldehyde) and with virtually total stereocontrol ( syn / anti ratio up to 99:1; ee up to 99 %). Some possibilities of further chemical elaboration of adducts are also briefly illustrated. Abstract : Propargylic Mannich adducts of syn relative configuration are now accessible in essentially diastereo‐ and enantiopure form from the direct reaction between aldehydes and C ‐alkynyl imines (see scheme), thus complementing previously reported methods to access the anti ‐adducts. The reactions are general and proceed in very mild conditions (CH2 Cl2, −20 °C) without formation of side products.